PEDIATRIC HAND BLAST INJURY PROFILE IN EMERGENCY ROOM OF DR. HASAN SADIKIN GENERAL HOSPITAL BANDUNG - Ismiarto, Yoyos Dias; Arif, Yoan Putrasos (Majalah Kedokteran Bandung, 2019)
In the past, blast injuries were mainly caused by war-related incidents. However, despite the current lack of war-related activities, blast injuries are still seen due to unintentional low explosive material blasts which are mostly seen on children?s hand. However, the classification for the severity of this type of injury is still unclear. The aim of this study was to assess the incident, patterns, and severity of hand blast injuries among pediatric patients treated in Dr.Hasan Sadikin General Hospital. Twenty two pediatric patients in Dr. Hasan Sadikin Hospital Bandung from 2013?2017 were included in this study. All data were extracted retrospectively from patient medical records and the degree of injury severity was assessed using Hand Injury Severity Score (HISS). There were 22 hand injuries caused by explosion identified in 18 boys (82%) with the age range of 5 to 15 years. Hand injuries from explosions have a specific pattern with the hand radial side experiencing the most severe damage including the thumb (16 cases), index finger (16 cases), and middle finger (14 cases). The severity of the injuries varied from mild (3 cases) to moderate (4 cases), severe (7 cases), and major (8 cases).  A high incidence of major hand blast injuries is found among pediatric patients with the hand radial side tends to suffer the most severe damage.Profil Cedera Tangan Akibat Ledakan pada Anak di Ruangan Gawat Darurat RSUP Hasan Sadikin BandungCedera akibat ledakan di masa lalu terutama disebabkan oleh situasi peperangan. Saat ini cedera akibat ledakan masih terjadi terutama pada tangan anak yang disebabkan oleh ledakan bahan berdaya rendah yang tidak disengaja. Namun, klasifikasi untuk menentukan derajat keparahan cedera masih belum jelas. Tujuan dari penelitian ini adalah menganalisis insidensi, pola, dan derajat keparahan cedera terhadap pasien yang dirawat di Rumah Sakit Hasan Sadikin. Penelitian ini melibatkan 22 pasien anak di Rumah Sakit Dr. Hasan Sadikin Bandung periode 2013-2017. Semua data didapatkan secara retrospektif dari rekam medis pasien. Tingkat keparahan cedera dinilai menggunakan Hand Severity Severity Score (HISS). Dua puluh dua cedera tangan akibat ledakan teridentifikasi. Kelompok ini sebagian besar terdiri atas 18 anak laki-laki dengan rentang usia 5 hingga 15 tahun. Cedera tangan akibat ledakan memiliki pola tertentu, dengan sisi radial tangan mengalami kerusakan paling parah di antaranya 15 kasus mengenai ibu jari, 16 kasus mengenai jari telunjuk, dan 14 kasus mengenai jari tengah. Tingkat keparahan cedera bervariasi dari kasus ringan sebanyak 3 kasus, sedang sebanyak 4 kasus, berat sebanyak 7 kasus, dan parah sebanyak 8 kasus. Cedera ledakan di tangan anak memiliki angka kejadian yang tinggi dalam kategori berat dengan sisi radial tangan cenderung menderita kerusakan paling parah.